Bridal Shower: Tren Perayaan Melepas Masa Lajang di Kalangan Perempuan di Kota Makassar - Astina Astina (Universitas Muslim Maros, 2020)
Bridal shower is a celebration of letting go of single status adopted from European and American culture. This has become a new form of ceremony held by a friendship group, as the bridesmaids. It examines the adoption process of bridal shower, the process of the celebration itself, and the meaning of such celebration from both bridesmaids and bride to be. This qualitative research was conducted in the capital city of Makassar, It involved 14 informant whose age between 21 and 26 years. They consist of eight bridesmaids who make and plan a bridal shower, four bride to be who have received a surprise bridal shower celebration, and two party planners who have five years experience in organizing such celebration. Data was collected using the combination of in-depth interview and observation, examining 18 cases of bridal shower celebration. The study indicates that bridal shower is conducted as a moment of separation and as a form of support from bridesmaids to the bride to be who will be heading to a new life. The reasons behind the celebration of bridal shower includes the presence of group awareness, moment of letting go of friend, as a form of group support, following trend, and as a form of reciprosity. The celebration of bridal shower includes five stages. First, welcoming bride to be with a number of surprises. Second, embedding of attributes with the use of a crown to show the privileges of the bride to be and a shawl as a medium for writing funny messages that generally relate to the transfer of status and sexuality. Third, playing games in the form of questions with sanctions. Fourth, disclosing messages and impressions from the bridesmaid to the bride to be; Fifth, ending up eating together while reminiscing. Although each stage has its own purpose, they are all meant to make the bride to be happy. Bridal shower celebration is full of meanings, namely: as a status switch, as a medium for self reflection and introspection, and as a moment for friendship group existence. Bridesmaids support is very significant considering that the transition from one status to another and incoming new responsibilities both create fears to the bride to be. Thus, bridal shower celebrations become a transitional ritual at the critical moment because, on the one hand, bride to be has already